Pelatihan Desain Aplikasi Canva di PKBM Tunas Harapan Surabaya - Evi Rizqi Salamah; Subaidah Subaidah; Denok Julianingsih (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
PKBM Tunas Harapan Surabaya, is one of the non-formal institutions in Surabaya, with one of its programs namely skills training and life skills. To support the program, the community service team (PkM) made observations regarding the implementation of activities in Tunas Harapan PKBM. This is intended to be a consideration for teachers to determine teaching materials and methods as well as the latest content to be used so that the information provided to students can be maximized. Canva's design training focuses on introducing, equipping, and implementing. In Tunas Harapan PKBM training participants. The activity contains the delivery of materials and practices for making Canva designs. The results obtained are the results of participants' designs and creativity. By knowing the results of the student work, the PkM team can provide reports to teachers and the Head of Institutions to be able to compile teaching materials and choose the right methods, materials, or content to be used by all participants in order to equip life skills and develop creativity and talents and interests of all participants.